2012
DOI: 10.1371/journal.pone.0048310
|View full text |Cite
|
Sign up to set email alerts
|

Autoinducers Act as Biological Timers in Vibrio harveyi

Abstract: Quorum sensing regulates cell density-dependent phenotypes and involves the synthesis, excretion and detection of so-called autoinducers. Vibrio harveyi strain ATCC BAA-1116 (recently reclassified as Vibrio campbellii), one of the best-characterized model organisms for the study of quorum sensing, produces and responds to three autoinducers. HAI-1, AI-2 and CAI-1 are recognized by different receptors, but all information is channeled into the same signaling cascade, which controls a specific set of genes. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 65 publications
9
57
0
1
Order By: Relevance
“…However, unlike our model, it does not offer a rationale for investment in these molecules, which are arguably better interpreted as by-product cues that may advertise a cell's presence to competitors instead of being a signal in an evolutionary sense (21). More recently, it has been proposed that, if autoinducers naturally accumulate in a sequential order during single-species population growth, bacteria can distinguish phases in population development from total signal concentration (22,23). A last possibility is that multiple signals simply allow for multiple thresholds for gene expression if bacteria require information on multiple-density thresholds (24).…”
Section: Discussionmentioning
confidence: 96%
“…However, unlike our model, it does not offer a rationale for investment in these molecules, which are arguably better interpreted as by-product cues that may advertise a cell's presence to competitors instead of being a signal in an evolutionary sense (21). More recently, it has been proposed that, if autoinducers naturally accumulate in a sequential order during single-species population growth, bacteria can distinguish phases in population development from total signal concentration (22,23). A last possibility is that multiple signals simply allow for multiple thresholds for gene expression if bacteria require information on multiple-density thresholds (24).…”
Section: Discussionmentioning
confidence: 96%
“…The consequences of manipulation of Vibrio QS with the cyanobacterial compound lyngbic acid are not yet known. In Vibrio spp., QS signals act as timers, with the CqsS/CAI-1 system active at low population densities (Henke and Bassler, 2004;Anetzberger et al, 2012). In concert with other QS signals, the CqsS/CAI-1 system regulates toxin and metalloprotease production, as well as type 3 secretion system (Henke and Bassler, 2004;Higgins et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There was a gradual increase in the intensity of HAI-1 throughout the growth curve, indicating an accumulation in the media, although there is a sharper increase during the 20-24 hour interval. The concentration of HAI-1 was low compared to other molecules detected, which agree with findings by Anetzberger et al (2012), which showed that the concentrations of autoinducers vary depending on the growth phase. The study showed that HAI-1 and CAI-1 activities becomes more prominent later during stationary phase, and that AI-2 concentration accumulates early during growth, peaks during mid-exponential growth phase and eventually declines during stationary phase.…”
Section: Results a Vibrio Harveyi Growth Curvesupporting
confidence: 90%